A4GALT-targeting siRNA lipid nanoparticles ameliorate Fabry disease phenotype: Greater efficacy in endothelial cells than in podocytes - Yoo Jin Shin; Hanbi Lee; Xianying Fang; Sheng Cui; Sun Woo Lim; Kang In Lee; Jae Young Lee; Hong Lim Kim; Yuna Oh; Can Li; Chul Woo Yang; Gayeon You; et al. (Molecular Therapy: Nucleic Acids)
In this study, we explore the therapeutic feasibility of globotriaosylceramide (Gb3) synthase (A4GALT)-specific siRNA-loaded polyhistidine (pHis)-incorporated lipid nanoparticles (HLNPs) for Fabry disease (FD). HLNPs were developed to deliver siRNAs targeting A4GALT using a microfluidic device, with pHis aiding in endosome escape. The therapy was tested on GLA-knockout human-induced pluripotent-stem-cell-derived endothelial cells (GLA-KO-hiPSC-ECs) and podocytes (GLA-KO-hiPSC-PCs). GLA-KO-hiPSCs-ECs or -PCs, upon differentiation, were treated with A4GALT-siRNA-HLNP. Successful intracellular uptake of A4GALT-siRNA-HLNP was confirmed through fluorescence and electron microscopy in both cell types. A4GALT-siRNA-HLNP treatment confirmed both cell types’ stability at 5 μg/mL. Increased Gb3 deposition and zebra body formation were detected in both cell types, but A4GALT-siRNA-HLNP treatment attenuated these FD phenotypes, demonstrating reduced expression of A4GALT through western blot analysis. RNA sequencing analysis revealed that the expression of transcripts associated with FD was restored by A4GALT-siRNA-HLNP treatment in GLA-KO-hiPSCs-ECs, whereas in GLA-KO-hiPSCs-PCs, this effect was relatively less pronounced. Suppression of A4GALT via siRNA/HLNP treatment significantly rescued FD phenotypes especially in EC, presenting a novel therapeutic approach for FD.